Legal Protection For Platform User Who Are Harmed By Data Leaks In E-Commerce And Prevention Efforts By The Government - Al Ikhsan, Muhammad Iqbal; Zubaedah, Rahmi (International Journal of Education, Information Technology, and Others, 2024)
Personal data is what is most needed to process or carry out transaction activities on digital platforms. In processing, storing and managing personal data, it is not uncommon for failures in the system to result in personal data being leaked due to the inability of the electronic organizer to process the data, the electronic organizer's system being inadequate and a lack of security in the system. This research aims to determine the factors that cause leaks of personal data of platform users in e-commerce, legal protection for digital platform users who are accused of personal data leaks, and government efforts to reduce leaks of users' personal data in e-commerce. This research uses a normative juridical approach, namely an approach based on the main legal materials by examining legal principles, legal systematics and legal comparisons. Based on the research results, it can be concluded that the factors causing the leak of personal data of platform users in e-commerce are due to the lack of implementation of regulations, supervision of system suitability, education regarding the importance of protecting personal data, and cyber space security that is not well controlled, and the existence of forms of cyberspace threats. Preventive legal protection efforts in article 16 of Law Number 27 of 2022 concerning Protection of personal data, Article 26 paragraph (1) of Law Number 19 of 2016 concerning Electronic Information and Transactions, Article 33 Paragraph (2) of Government Regulation Number 80 of 2016 2019 Concerning Trading Through Electronic Systems. Repressive legal protection for users can be resolved through litigation or non-litigation based on Article 60 of the Personal Data Protection Law. The government's efforts to reduce data leaks include regulation, supervision and control, providing education, and securing cyberspace.